2019
DOI: 10.4187/respcare.06812
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial Comparing Two Lung Expansion Therapies After Upper Abdominal Surgery

Abstract: BACKGROUND: Lung expansion therapy is often ordered after surgery to improve alveolar ventilation and reduce risks of postoperative pulmonary complications. The impact of lung expansion therapy at altering ventilation in patients who are not intubated has not been described. The primary purpose of this study was to determine if there is a difference in dorsal redistribution of ventilation and incidences of postoperative pulmonary complications when comparing incentive spirometry (IS) with Ez-PAP lung expansion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…In patients at risk of hypoxemia, the EzPAP improved pulmonary oxygenation ( Rieg et al, 2012 ). Another trial compared incentive spirometry to EzPAP in 112 postoperative patients, and found no differences between the two strategies in terms of lung expansion or postoperative pulmonary complications ( Rowley et al, 2019 ). As for other techniques, data are limited in COVID-19.…”
Section: Chest Physiotherapy For Mechanically Ventilated Covid-19 Patmentioning
confidence: 99%
“…In patients at risk of hypoxemia, the EzPAP improved pulmonary oxygenation ( Rieg et al, 2012 ). Another trial compared incentive spirometry to EzPAP in 112 postoperative patients, and found no differences between the two strategies in terms of lung expansion or postoperative pulmonary complications ( Rowley et al, 2019 ). As for other techniques, data are limited in COVID-19.…”
Section: Chest Physiotherapy For Mechanically Ventilated Covid-19 Patmentioning
confidence: 99%
“…It has been demonstrated that high levels of positive end-expiratory pressure (15 cmH 2 O) are beneficial for the improvement of gas exchange in those patients [62]. This technique has also been evaluated in patients after upper abdominal surgery, and no significant differences in lung expansion or post-operative pulmonary complications were observed compared with incentive spirometry [63].…”
Section: Techniques For Lung Expansionmentioning
confidence: 99%
“…E-mail: thomaspiraino@gmail.com. DOI: 10.4187/respcare.07402 inspiratory distribution) information is important, although not reported by Rowley et al 6 In fact, it should be noted that the distribution of ventilation referred to in their paper refers to distribution of the ⌬EELI, not the distribution of tidal volume (represented by tidal variation with EIT). Tidal variation is used to describe the change in ventilation to an area and changes in regional compliance, which is quite different than ⌬EELI, which represents the changes in end-expiratory level only.…”
mentioning
confidence: 91%
“…In this issue of RESPIRATORY CARE, Rowley et al 6 randomized 112 subjects to receive either IS or EzPAP for 5 d after upper abdominal surgery. The authors wanted to determine if there was a significant change in end-expiratory lung impedance (⌬EELI) in the dorsal lung regions after lung expansion therapies.…”
mentioning
confidence: 99%
See 1 more Smart Citation